Introduction to Quantum Field Theory - Casalbuoni, Roberto (Singapore : Wsp, 2011)
This book deals with quantum field theory, the language of modern elementary particles physics. Based on university lectures given by the author, this volume provides a detailed technical treatment of quantum field theory that is particularly useful for students; it begins with the quantization of the most important free fields, the scalar, the spin-1/2 and the photon fields, and is then followed by a detailed account of symmetry properties, including a discussion on global and local symmetries and the spontaneous breaking of symmetries. Perturbation theory, one-loop effects for quantum electrodynamics, and renormalization properties are also covered.
Included Bibliography 263-266p.; Index 267-273p.
Keywords: Dirac and Vector fields; Field theory; Perturbation theory; Quantum field theory; Physics